If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8t + -14 = 0 Reorder the terms: -14 + 8t = 0 Solving -14 + 8t = 0 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + 8t = 0 + 14 Combine like terms: -14 + 14 = 0 0 + 8t = 0 + 14 8t = 0 + 14 Combine like terms: 0 + 14 = 14 8t = 14 Divide each side by '8'. t = 1.75 Simplifying t = 1.75
| 8m+3n-3m+10n= | | 48x^2-1537x-3076= | | 9x^2-2x^3=0 | | 3f^2+2f-f^2+4f= | | x^3+3x^2-8x+4=0 | | (x+9)2=81 | | 5+y=2y-4 | | 5x^2-30x+9-20x^2-25x+20x^2+5x-5x^2= | | 3x+15=11-x | | 5x*(x-1)= | | 5x*(4x-5)= | | 3x+5=11-x | | Log(11-x)-log(2-x)=1 | | X^4-8x^3+18x^2-8x-1=0 | | 2xsquared-16=0 | | 9(x-6)=4x | | 25=(3x-2)(2x+5)(3x-2)2 | | 25=(3x-2)(2x+5)(3x-2) | | 8x-7w+5x+8y+5y+3w= | | 5x-3=x+7+3 | | 137+x=428 | | X^3+4x^3+4x=0 | | 5y-8=22-y | | 10x+5y+7z-5x+3z-9y= | | 11a-16=6a-1 | | 4y-14=18whatisy | | 8t+2=3t+12 | | 6.5=2x+3 | | 5+2x=5x-3(x-1)+2 | | x+(x-7)=67 | | 6x^3+x^2-35x=0 | | 5x-2=11x+5-6x |